Application Of Passage Plan To Avoid Ship Aground In Barito River: Case Study On Km. Fleet Fresh - Kumoro Jati, Septria; Iskandar; Nurhidayati, Indah (LPPM AKMI SUAKA BAHARI CIREBON, 2025)
In the world of shipping, passage plans play an important role in improving the efficiency and safety of ship operations when sailing, so that narrow shipping channels are very useful because there are many dangerous areas of navigation in these areas. Ship incidents are often caused by external factors such as weather and track conditions, as well as human error in the operation of the ship. The passage plan is the most common strategy that aims to direct ships from one location to another safely, quickly, and efficiently. This study, entitled